The Acquisition of Vocabulary by Using Children Song and Kinesthetic Learning Strategy in Bali Public School - Suhcera, Aridna (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p16, 2018)
Many learning strategies were made in order to enrich children’s vocabulary. The present research is aimed at seeing if a great combination of learning strategy could affect children in acquiring vocabulary. The research was using a combination of children song and kinesthetic learning strategy to acquire vocabulary. The subject of the research was the second grade students of Bali Public School with 3 samples from Class A and Class B. Group A was using the combination of children song and kinesthetic learning strategy and Group B was using children song alone without kinesthetic learning strategy. The data were obtained through pre-test and post-test that consist of multiple choice questions. The obtained data were analyzed quantitatively and qualitatively. Furthermore, the data are presented using formal (words and natural language) and informal (table and diagrams) methods. The vocabulary that the children had acquired through this combination included adjective, verbs, collective nouns and countable nouns. The process of acquiring vocabulary through kinesthetic learning strategy on the second grade students included the symbolic, centration and elimination of egocentrism process.